ab initio Calculations and Mechanism of 1,3-Dipolar Additions on ethylene - ABDUL JALEEL, P.K.; ZEINUL HUKUMAN, N.H. (Asian Journal of Chemistry, 2010)
ab initio calculations for the dipolar addition of ethylene with CNO, N2O, ONO and O3 have been carried out using hybrid density functional B3LYP and moller plesset energy correlation MP2 with aug-cc- PVDZ basis sets using Gaussian 03 suite of programmes. A cyclic Diels Alder type mechanism is suggested for N2O and CNO and a fragmented one for ONO and O3 using geometry optimization and harmonic vibrational frequencies. The shift in mechanism is due to difference in the ambivalent character of dienophiles.